Effects of organizational justice and psychological safety on knowledge hiding and employee creativity - Nam, Tran The; Mai, Che Thi Thanh; Thuy, Ho Thi Thanh; Ca, Phan Thi My; Uyen, Vo Hoang Kim (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
In the era of a knowledge-based economy, the innovative behavior of employees is essential to lead to the success of any organization, including banks. However, after COVID-19, all businesses are facing difficulties and must decrease the number of workers. Therefore, employees feel insecure and hide knowledge from others to keep their jobs. How to reduce knowledge hiding and increase employee creativity is an interesting question for both researchers and managers. Based on the conservation of resources theory and social exchange theory, the authors build the research model to analyze the influences of employees’ perceptions of organizational justice and psychological safety on employees’ knowledge hiding and creativity. The mixed method is used with PLS-SEM analysis to analyze the data of 195 respondents. The results of research confirmed the great impacts of perceived organizational justice and psychological safety on staff’s knowledge hiding and innovative behaviors. In practice, managers should provide more justice in all three aspects (procedures, communication, income). Moreover, open communication between all members of an organization is a good way to increase the mind’s creativity.